Go-to-market strategies for women entrepreneurs : creating and exploring success - Crittenden, Victoria L. (Emerald Publishing Limited, 2019)
The role of women in business and society is beset with traditions and expectations that leave women's ambitious desires unfulfilled. And yet, with the rise of the female entrepreneur, this is changing.Entrepreneurship expert Victoria L. Crittenden, along with a cast of first-rate global contributors, provides a lens into the power of women entrepreneurship. From home businesses and Mompreneurs, to women-led global businesses such as The Body Shop and Ceja Vineyards, chapters explore the role woman entrepreneurship plays in building self-efficacy, the power of creating and utilizing social capital, the importance of being authentic and true to one's self, and the value of family, friends, mentors, and role models. By discussing ideas such as the ecosystem of radical generosity, where women are recognized for their talents and where women help each other to succeed, Crittenden and her contributors show the power of empowerment -- empowerment that can positively impact the social and fiscal health of nations through better education, poverty reduction, and decreased violence.For researchers and students of entrepreneurship, this is an unmissable book exploring the positive societal impact and strong economic effects of female empowerment. Through discussing case studies of some of the most successful and powerful women over the last fifty years, this book acts as both an inspiration for women just setting out on their own entrepreneurial journey and validation to those women who have already encountered the ups and downs of their entrepreneurial endeavors.